Research progress and trends of deep learning based wireless communication receiving method - Panpan LI; Zhengxia XIE; Guangxue YUE; Xin LIU (Dianxin kexue)
With the continues expansion of the application boundary for wireless communications, the application environment of wireless communications is becoming increasingly complex and diverse, which faces negative impacts such as radio frequency (RF) damage, channel fading, interference and noise.It brings difficulties to recover the original information at the receiver.Drawing from the research results of deep learning methods in computer vision, pattern recognition, natural language processing and other fields, wireless communication reception technology based on deep learning has received wide attentions from both academia and industry.Firstly, the current research status of wireless communication reception technology based on deep learning at home and abroad was described.Secondly, the current technical challenges of wireless communication reception in the context of signal big data were outlined, and a reference architecture of intelligent wireless communication reception based on deep neural network was proposed.Finally, the development trend of intelligent wireless communication reception method in the context of signal big data was discussed.It is expected to provide reference for the research and development of wireless communication technology based on deep learning.